Assay Guidance Manual: Quantitative Biology and Pharmacology in Preclinical Drug Discovery. Issue 5 (24th July 2018) - Coussens, Nathan P.; Sittampalam, G. Sitta; Guha, Rajarshi; Brimacombe, Kyle; Grossman, Abigail; Chung, Thomas D. Y.; Weidner, Jeffrey R.; Riss, Terry; Trask, O. Joseph; Auld, Douglas; Dahlin, Jayme L.; Devanaryan, Viswanath; et al.
Abstract: The Assay Guidance Manual (AGM) is an e Book of best practices for the design, development, and implementation of robust assays for early drug discovery. Initiated by pharmaceutical company scientists, the manual provides guidance for designing a "testing funnel" of assays to identify genuine hits using high‐throughput screening (HTS) and advancing them through preclinical development. Combined with a workshop/tutorial component, the overall goal of the AGM is to provide a valuable resource for training translational scientists .